Using Web-Based Technology to Promote Physical Activity in Latinas. Issue 7 (July 2015) - BENITEZ, TANYA J.; CHERRINGTON, ANDREA L.; JOSEPH, RODNEY P.; KELLER, COLLEEN; MARCUS, BESS; MENESES, KAREN; MARQUEZ, BECKY; PEKMEZI, DOROTHY
<x xml:space="preserve">Abstract</x> Latinas in the US report high levels of physical inactivity and are disproportionally burdened by related health conditions (eg, type 2 diabetes, obesity), highlighting the need for innovative strategies to reduce these disparities. A 1-month single-arm pretest-posttest design was utilized to assess the feasibility and acceptability of a culturally and linguistically adapted Internet-based physical activity intervention for Spanish-speaking Latinas. The intervention was based on the Social Cognitive Theory and the Transtheoretical Model. Changes in physical activity and related psychosocial variables were measured at baseline and the end of the 1-month intervention. The sample included 24 Latina adults (mean age, 35.17 ± 11.22 years). Most (83.3%) were born outside the continental US. Intent-to-treat analyses showed a significant increase (P = .001) in self-reported moderate- to vigorous-intensity physical activity from a median of 12.5 min/wk at baseline to 67.5 min/wk at the 1-month assessment. Participants reported significant increases in self-efficacy as well as cognitive and behavioral processes of change. Nearly half of the participants (45.8%) reported advancing at least one stage of change during the course of the 1-month intervention. Findings support the feasibility and acceptability of using interactive Internet-based technology to promote physical activity among Latinas in Alabama.